2012
DOI: 10.1590/s1806-37132012000600005
|View full text |Cite
|
Sign up to set email alerts
|

Potenciais impactos da variabilidade climática sobre a morbidade respiratória em crianças, lactentes e adultos

Abstract: Objective: To determine whether climate variability influences the number of hospitalizations for respiratory diseases in infants, children, and adults in the city of Campo Grande, Brazil. Methods: We used daily data on admissions for respiratory diseases, precipitation, air temperature, humidity, and wind speed for the 2004-2008 period. We calculated the thermal comfort index, effective temperature, and effective temperature with wind speed (wind-chill or heat index) using the meteorological data obtained. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 13 publications
(13 reference statements)
0
14
0
18
Order By: Relevance
“…In a Brazilian study, the combination of rainfall, air temperature, humidity and wind speed showed relatively high correlation coefficients in relation to hospital admissions for pneumonia in children (R 2 = 68.4%) and infants (R 2 = 71.8%) [ 51 ].…”
Section: The Impact Of Climate Change On Paediatric Respiratory Inmentioning
confidence: 99%
“…In a Brazilian study, the combination of rainfall, air temperature, humidity and wind speed showed relatively high correlation coefficients in relation to hospital admissions for pneumonia in children (R 2 = 68.4%) and infants (R 2 = 71.8%) [ 51 ].…”
Section: The Impact Of Climate Change On Paediatric Respiratory Inmentioning
confidence: 99%
“…(3) Unary linear regression prediction is a method to establish the linear regression equation However, linear regression results are easy to explain natural processes of respiratory infectious diseases caused by viruses and are of great significance. (Kim et al, 2016;Lim et al, 2012;Souza et al, 2012;Onozuka et al, 2009).…”
Section: Regression Analysis Of Incremental Cases and Meteorological mentioning
confidence: 99%
“…Through case cross design, personal characteristics and long-term and seasonal trends can be controlled (Lim et al, 2012). GLM was also used in the studies of Onozuka et al and Souza et al (Souza et al, 2012;Onozuka et al, 2009). For seasonal viral infectious diseases, Gurgel et al and Yusuf et al used time series analysis to reduce model deviations (Gurgel et al, 2016;Yusury et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As doenças respiratórias foram mais prevalentes em grupos populacionais com características definidas, como grupo etário, doenças autorreferidas, tipo de moradia e obesidade. Souza et al (2012) estudaram a relação existente entre a o número de internações por doenças do aparelho respiratório em lactentes, crianças e adultos e as variações meteorológicas na cidade de Campo Grande (MS). Foram utilizados dados diários de internações por doenças respiratórias, precipitação, temperatura do ar, umidade e velocidade dos ventos entre 2004 e 2008.…”
Section: De Acordo Comunclassified